Exploring Semaglutide Effects on Osteoarthritis in Obesity: Emphasis on Weight Management and Inflammatory Responses - Ravi, Priyadharsini; Ravi, Priyadharsini; Ismail, Rabiyath Riswana; Jayaprakash, Subiksha; Arumugam, Prathap (Indian Journal of Pharmacy Practice)
Obesity frequently makes Osteoarthritis (OA), a degenerative joint disease, worse by increasing systemic inflammation and mechanical stress. Semaglutide is a medicine that helps people with type 2 diabetes and obesity. It works by making people lose weight. Recently, many researchers have been looking into how it might help in other ways. They want to know if it can be used for more than just weight loss and diabetes treatment. Semaglutide dual function in slowing the course of OA by encouraging substantial weight loss and modifying inflammatory pathways is examined in this review. Recent data indicates that semaglutide – induced weight loss reduces joint load, and its anti-inflammatory qualities may have a direct impact on the pathophysiology of OA. Gaining insight into these processes may help develop combined therapy plans that address OA and obesity.
Keywords: Semaglutide; Osteoarthritis; Obesity; Weight loss; T2DM